Removal of perchlorate in water by calcined MgAl-CO3 layered double hydroxides - Yang, Yiqiong (Water environment research : a research publication of the Water Environment Federation, 2013)
Perchlorate is widely known as an inorganic endocrine disruptor. In this study, MgAl-CO3 layered double hydroxides with different Mg/Al molar ratios were prepared using a coprecipitation method and followed by a calcination process at a temperature range of 300 to 700 degrees C. Results showed that the best synthesis conditions were a calcination temperature of 550 degrees C and Mg/Al molar ratio of 3. Further, the adsorbent and its adsorption product were characterized by x-ray diffraction, Fourier transform-infrared spectroscopy, and thermogravimetric-differential thermal analysis. The layered double hydroxides structures in the adsorbent were lost during calcination at 550 degrees C but were reconstructed subsequent to adsorption of perchlorate, indicating that the "memory effect" appeared to play an important role in perchlorate adsorption. The perchlorate adsorption pattern was best described by the pseudo-second-order kinetics model, while the Freundlich isotherms appropriately explained perchlorate adsorption data